The significance of conventional radiographic parameters in the diagnosis of scapholunate ligament lesions - Megerle, Kai Oliver; Pöhlmann, Sebastian; Kloeters, Oliver; Germann, Günter; Sauerbier, Michael (European radiology, 2011)
Objective: Although in widespread clinical use, evidence of the diagnostic accuracy of radiographic parameters for the diagnosis of scapholunate ligament injuries is scarce. The objective of this study was to evaluate the scapholunate (SL) angle, radiolunate (RL) angle and SL gap as diagnostic parameters for these lesions. Methods: Eight hundred forty nine patients, who underwent wrist arthroscopy at our institution because of wrist pain were included in a retrospective analysis. In all patients the SL angle, RL angle and SL gap were measured on preoperative radiographs. These parameters were correlated with the actual finding of the SL ligament during arthroscopy. Optimal test thresholds were calculated as well as sensitivity, specificity and the likelihood ratios of each parameter. Results: All three parameters proved useful in statistical analysis. The optimal cut-off points for diagnosing lesions of the SL ligament were calculated as 62.5° for the SL angle, 12.5° for the RL angle and 2.5 mm for the SL gap. SL angles had the greatest specificity (0.93). Conclusions: We were able to validate plain radiographs as a reliable tool in the work-up of patients with suspected SL ligament injuries. However, wrist arthroscopy remains the gold standard in diagnosing and treating these lesions.
Published online: 5 August 2010
Gesehen am 16.08.2022